2021
DOI: 10.3390/cells10051236
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Diabetes Mellitus in Alzheimer’s Disease

Abstract: Type 2 diabetes mellitus is a progressive disease that is characterized by the appearance of insulin resistance. The term insulin resistance is very wide and could affect different proteins involved in insulin signaling, as well as other mechanisms. In this review, we have analyzed the main molecular mechanisms that could be involved in the connection between type 2 diabetes and neurodegeneration, in general, and more specifically with the appearance of Alzheimer’s disease. We have studied, in more detail, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 435 publications
(465 reference statements)
3
63
1
5
Order By: Relevance
“…Thus, under physiological conditions, insulin acts as a protective factor for brain function and contributes to the prevention of cognitive decline. On the other hand, a dysregulated brain insulin signaling, defined as “brain insulin resistance”, has been proposed among factors responsible for AD progression [ 19 ], and the impaired activity of several mediators in the insulin-signaling pathways may contribute to neurodegeneration and AD symptoms [ 51 , 52 ].…”
Section: Insulin-signaling Impairment and Neurodegenerationmentioning
confidence: 99%
“…Thus, under physiological conditions, insulin acts as a protective factor for brain function and contributes to the prevention of cognitive decline. On the other hand, a dysregulated brain insulin signaling, defined as “brain insulin resistance”, has been proposed among factors responsible for AD progression [ 19 ], and the impaired activity of several mediators in the insulin-signaling pathways may contribute to neurodegeneration and AD symptoms [ 51 , 52 ].…”
Section: Insulin-signaling Impairment and Neurodegenerationmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most prevalent form of dementia [1] and it is also one of the most significant causes of morbidity and mortality in the elderly population worldwide [3]. AD prevalence is estimated to reach Pharmaceuticals 2021, 14, 890 2 of 22 115 million by 2050 due to an increased ageing population pattern, unless novel drugs are available to slow or cure this disease [2][3][4]. Neuropathological modifications of AD, such as tau hyperphosphorylation and Aβ toxicity, led to the main current hypothesis trying to explain neuronal and synapse loss, associated with cognitive and memory impairment [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been shown that both T2DM and LOAD possess multifactorial risk profiles and a wide variety of molecular connections. The intersection between the molecular pathways of these two diseases could give birth to the appearance of the cognitive anomalies of LOAD patients with underlying T2DM [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, brain insulin resistance may be defined as the failure of brain cells to respond to insulin [ 82 ]. Lack of response to insulin may be due to various causes, including downregulation of insulin receptors, the inability of IR to bind insulin or an impairment of the insulin cascade [ 83 ].…”
Section: Insulin Resistance and Alzheimer’s Diseasementioning
confidence: 99%
“…In brains characterized by AD, Tau protein demonstrates three times as much hyperphosphorylation than in normal brains [ 83 ]. Indeed, out of 85 phosphorylable residues, more than 40 phosphorylation sites have been identified in Tau from the brains of AD patients, and 28 sites are exclusively phosphorylated [ 95 ].…”
Section: Insulin Resistance and Alzheimer’s Diseasementioning
confidence: 99%